Antioxidant and hepatoprotective activities of the oil fractions from wild carrot (Daucus carota ssp. carota). (September 2015) - Shebaby, Wassim N.; Daher, Costantine F.; El-Sibai, Mirvat; Bodman-Smith, Kikki; Mansour, Anthony; Karam, Marc C.; Mroueh, Mohamad
Abstract Context: Wild carrot, Daucus carota L. ssp. carota (Apiacae), is widely distributed throughout the world and has various uses in traditional medicine in Lebanon. Objective: The present study aimed to fractionate and analyze the chemical composition of the Daucus carota oil extract (DCOE) fractions and to evaluate their antioxidant and hepatoprotective properties in vitro and in vivo. Materials and methods: DCOE was chromatographed on silica gel column to produce four fractions: pentane (F1), 50:50 pentane:diethyl ether (F2), diethyl ether (F3), and 93:7 chloroform: methanol (F4). Qualitative and quantitative analyses of oil fractions were performed by GC-MS and HPLC techniques. The in vitro antioxidant properties were assessed using DPPH, FIC, and ferric-reducing antioxidant power (FRAP) assays. The hepatoprotective property was determined by examining the levels of serum markers (alanine transaminase (ALT) and aspartate transaminase (AST)) and hepatic antioxidant (superoxide dismutase (SOD), catalase (CAT), and glutathione-S-transferase (GST)) enzymes in CCl4-intoxicated mice pretreated with intraperitoenal 50, 100, or 200 mg/kg b.w. of the oil fractions for 5 d. Results: GCMS analysis of F2 revealed the presence of 2-himachalen-6-ol (61.4%) which is reported for the first time in Daucus carota species. F3 and F4 were rich in phenolics and flavonoids and demonstrated significant DPPH activity (IC50 = 0.29 and 0.38 mg/ml, respectively) and high FRAP values (225.11 and 437.59 µmol FeSO4/g, respectively). The sesquiterpene-rich fraction F1 had the highest FIC ability (IC50 = 0.28 mg/ml). Pretreatment with F1 and F4 reversed the CCl4-induced decrease in SOD, CAT, and GST levels and reduced significantly hepatic damage. Discussion and conclusion: The current results suggested that wild carrot oil fractions exhibited a unique chemical composition and possessed significant antioxidant activities as well as hepatoprotective effects against CCl4-induced hepatotoxicity.